Grazing by an endemic atyid shrimp controls microbial communities in the Hawaiian anchialine ecosystem. Issue 9 (13th July 2022) - Havird, Justin C.; Brannock, Pamela M.; Yoshioka, Reyn M.; Vaught, Rebecca C.; Carlson, Kaile'a; Edwards, Collin; Tracy, Allison; Twining, Cornelia W.; Zheng, Yun; Chai, David; Wilson, Alan E.; Hairston, Nelson G.; et al.
Abstract: Animals often shape environmental microbial communities, which can in turn influence animal gut microbiomes. Invasive species in critical habitats may reduce grazing pressure from native species and shift microbial communities. The landlocked coastal ponds, pools, and caves that make up the Hawaiian anchialine ecosystem support an endemic shrimp ( Halocaridina rubra ) that grazes on diverse benthic microbial communities, including orange cyanobacterial‐bacterial crusts and green algal mats. Here, we asked how shrimp: (1) shape the abundance and composition of microbial communities, (2) respond to invasive fishes, and (3) whether their gut microbiomes are affected by environmental microbial communities. We demonstrate that ecologically relevant levels of shrimp grazing significantly reduce epilithon biomass. Shrimp grazed readily and grew well on both orange crusts and green mat communities. However, individuals from orange crusts were larger, despite crusts having reduced concentrations of key fatty acids. DNA profiling revealed shrimp harbor a resident gut microbiome distinct from the environment, which is relatively simple and stable across space (including habitats with different microbial communities) and time (between wild‐caught individuals and those maintained in the laboratory for >2 yr). DNA profiling also suggests shrimp grazing alters environmental microbial community composition, possibly through selective consumption and/or physical interactions. While this work suggests grazing by endemic shrimp plays a key role in shaping microbial communities in the Hawaiian anchialine ecosystem, the hypothesized drastic ecological shifts resulting from invasive fishes may be an oversimplification as shrimp may largely avoid predation. Moreover, environmental microbial communities may have little influence on shrimp gut microbiomes.